PENGEMBANGAN LAYANAN MODUL TEORI SOSIAL KOGNITIF BERBASIS TEKNIK MODIFIKASI PERILAKU UNTUK MENGATASI PERILAKU ISOLASI SOSIAL MAHASANTRI IBNU KATSIR 2 JEMBER - Baihaqi, Maghfiroh; Mudafiatun Isriyah; Nailul Fauziyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to help overcome social isolation behavior that occurs among students who can have a bad or negative impact on them. Social isolation is a behavior that is defined as a state where an individual feels separated or does not have meaningful social relationships with others. Social isolation can also be referred to as behavior that does not have the ability to interact with people around them, this is what causes an individual to prefer to close themselves off from the circumstances around them. As happened at PPA Ibnu Katsir, the results of observations and interviews by researchers concluded that this social isolation behavior can interfere with their learning activities while at the boarding school, and to overcome this, researchers are trying to develop a guidance and counseling service module book with a social cognitive theory approach to overcome social isolation behavior to make it easier for boarding school administrators to handle problems that occur in students. This strategy is carried out to help clients manage all aspects of life, especially in overcoming social isolation behavior. This study uses the R&D (research and development) method which will develop a product to help overcome social isolation behavior. The development process will use the ADDIE model as a guide in every step of product development. The purpose of this study is to create a product of guidance and counseling service module with a social cognitive theory approach to overcome social isolation behavior in students.